Ekuitas Merek Program Studi Agribisnis, Agroteknologi, dan Peternakan Universitas Padjadjaran - Dahlan Ramdhani (TRIKONOMIKA, 2014)
One of the problems of higher educations is the lack of interest of high school students to continue their studies to the study program related to agriculture. Lots of factors are considered to influence, wether it comes from the public, government or industry. Apart from the influence of government policy on higher education and labor economics, agricultural studies program managers should look at this as a chalenge to undertake the necessary efforts. One creative approach to provide solutions is marketing approach, especially brand equity approach. The selected study programs are Agribusiness, Agrotechnology and Animal Husbandry of Padjadjaran University. Respondents that are choosed group of high school students in Bandung. The study proposes that the brand equity of study program shows low score by high school school student respondents. Promotion, location and social image are factors that significantly affect students’s perception of brand equity study programs Agribusiness, Agrotechnology and Animal Husbandry of Padjadjaran University.This study use Part Least Square (PLS) in analysing data and specifying of variables inside.